A density functional theory study of the influence of exchange-correlation functionals on the properties of FeAs. (24th April 2017) - Griffin, Sinéad M; Spaldin, Nicola A
Abstract: We use density functional theory within the local density approximation (LDA), LDA + U, generalised gradient approximation (GGA), GGA + U, and hybrid-functional methods to calculate the properties of iron monoarsenide. FeAs, which forms in the MnP structure, is of current interest for potential spintronic applications as well as being the parent compound for the pnictide superconductors. We compare the calculated structural, magnetic and electronic properties obtained using the different functionals to each other and to experiment, and investigate the origin of a recently reported magnetic spiral. Our results indicate the appropriateness or otherwise of the various functionals for describing FeAs and the related Fe-pnictide superconductors.